PERAN PUBLIC RELATION UNIVERSITAS MUHAMMADIYAH SURAKARTA DALAM MEMBENTUK CITRA UNIVERSITAS MELALUI INSTAGRAM - Maurizka, Ella; Wisudawanto, Rahmat; Ningsih Rahayu Putri, Sofia (JURNAL KOMUNITAS, 2025)
Public Relations (PR) has an important role in institutional management because institutional management will not run well without its practitioners. A PR practitioner must have good technological understanding skills because he is required to build good relations with social media managed by the institution. This research was conducted at the Muhammadiyah University of Surakarta (UMS), using qualitative methodology, observation and interview techniques, and documentation. The data analysis technique was by means of data reduction, data presentation, and drawing conclusions. The results of the study showed that UMS PR had carried out its role well as a liaison between community groups and institutions. The role as a corporate image is the most dominant role. This can be observed from PR uploads on the Instagram page @umsofficialid which highlights the collaboration between UMS and other parties. Meanwhile, the role as back up management is a less dominant role. A positive image can be produced and in accordance with community expectations